2018
DOI: 10.1186/s12889-018-5576-5
|View full text |Cite
|
Sign up to set email alerts
|

Location influences snacking behavior of US infants, toddlers and preschool children

Abstract: BackgroundCompare at-home and away-from-home snacking patterns of US infants and young children.MethodsA secondary analysis was conducted using nationwide, cross-sectional dietary survey data from the US Feeding Infants and Toddlers Study (FITS) 2008. The sample included infants (6–11.9 months, n = 505), toddlers (12–23.9 months, n = 925), preschool children (24–47.9 months, n = 1461). Weighted population descriptive statistics (means and standard errors) were calculated using SAS. Significance was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(36 reference statements)
0
6
0
1
Order By: Relevance
“…The propensity of adults to snack away from home, especially at work, highlights the opportunity for health promotion initiatives encouraging healthy food and drink availability at work. Several studies have previously reported the number or proportion of snacks consumed at home and away from home by children and adolescents [7,[15][16][17][18][19]. Our results revealed that children, especially older ones (6-12 years), tended to consume more snacks away from home (about 38%) than other age groups.…”
Section: Discussionmentioning
confidence: 46%
“…The propensity of adults to snack away from home, especially at work, highlights the opportunity for health promotion initiatives encouraging healthy food and drink availability at work. Several studies have previously reported the number or proportion of snacks consumed at home and away from home by children and adolescents [7,[15][16][17][18][19]. Our results revealed that children, especially older ones (6-12 years), tended to consume more snacks away from home (about 38%) than other age groups.…”
Section: Discussionmentioning
confidence: 46%
“…Some data indicate that snacks consumed outside of the home, particularly in the afternoon, may represent important contextual targets for addressing snack quality and size. Data from the 2008 Feeding Infants and Toddlers study revealed that US toddlers and preschoolers consume more calories from snacks eaten away from home than at home [40]. Among children 4–13 years participating in 2009–2012 NHANES, afternoon snacking occasions were the most energy-dense and least nutrient-dense [9].…”
Section: Discussionmentioning
confidence: 99%
“…While consumption of food away from home is associated with greater weight gain over time and poorer diet quality in children and adolescents ( Powell and Nguyen, 2013 ), the prevalence of snacking at home versus away from home among US adolescents is presently unknown. While snacking at home has been reported to be more prevalent than snacking away from home in 13–18 year-old Canadians (74%) ( Vatanparast et al, 2020 ), the prevalence of snacking at home versus away from home among U.S. children and adolescents has been documented only in toddlers (73% at home) and preschoolers (67% at home) ( Jacquier et al, 2018 ). Furthermore, the contribution of snacks consumed at home versus away from home to intakes of added sugars, saturated fats, and sodium has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%